DIY photometer in determining the beginning of dawn time in Cimahi City - Cahyo Puji Asmoro; Hana Susanti; Judhistira Aria Utama; Dhani Herdiwijaya (Universitas Sultan Ageng Tirtayasa, 2024)
The use of SQM as a calibrated portable photometer is currently a hot topic in astronomical research in terms of measuring the brightness of the night sky; DIY Sky Quality Meter (SQM) with the name Photometer D.I.Y – CJ'01 has been successfully made and tested on a limited basis, the output data obtained by the photometer This is the magnitude value per square arc second (mag/sq arc second mpsas). This research aims to determine the performance of the D.I.Y - CJ'01 Photometer in measuring the night sky's brightness to determine the start of dawn. The research method used was an experiment with data collection from the D.I.Y Photometer – CJ'01 and SQM Unihedron in Cimahi City during the New Moon and Full Moon. The results of data processing using the solver method show that the D.I.Y - CJ'01 Photometer has almost the same performance as the SQM Unihedron based on the inflection point value that determines the start of dawn and also indicates the existence of pseudo-night in the city of Cimahi which is by typical urban areas dominated by light pollution and air pollution